O comércio informal em Feira de Santana (BA) : permanências e mudanças - Teles, Alessandra Oliveira (2017)
Informal trade in Feira de Santana, specially the one located on the streets downtown, has gone through significant changes from the beginning of the organization of the city with the street market and the cattle fair up to the city’s present organization with predominant industrialized products. The situation indicates that processes of capital accumulation have been included in the activity. The organization and relevance of such activity is the reflex of the power it possesses when it comes to attracting a great flow of people, mostly from the city’s micro region, and of the capacity of promoting the circulation of capital, characterizing the commercial center as a venue of great value for any kind of informal trade, including street market. Commerce is the strength of Feira de Santana’s economy. In this perspective, informal trade has become the focus of this study, considering its relevance. Continuity and changes in street trade in Feira de Santana are local result of global situation. Changes in the international scenario stablished over a short period of time will reset nations and cause significant economic and political changes in the contemporary world. The practice of street trade is a well-known model which gained new patterns if we consider what is commercialized presently since the street market is responsible, mostly, for commercializing agricultural or manufactured products. At the present organization, industrial production, mostly technological, is dominant in this kind of commerce. It is the result of a consolidating historic process, governmental actions, labor laws, as well as changes in production and labor relations at global level with local repercussions which resulted in a process of production restructuration. Furthermore, many citizens make a living out of this activity and many industries increase their capital by selling part of their production to this segment of commerce. Among continuity and changes, it is noticed that the street trade studied follows the logic and model of the society for which it is destined. In this context, trade conducted by street vendors has reflected clients’ needs and interests. The conclusion of this research shows that informal trade in Feira de Santana presents great heterogeneity, complexity and relevance for society and economy. Therefore, continuity and changes in the activity allow several further studies.